Ethnic conflicts in Southeast Asia - Kusuma Sanitwong Na Ayutthaya; Thompson, W. Scott (Willard Scott) 1942- (Gale virtual reference library, 2005)
Collection of papers looking at the avoidance and resolution of ethnic conflicts in five Southeast Asian countries: Indonesia, Malaysia, Myanmar [Burma], Philippines, and Thailand.